Detection and identification of azithromycin resistance mutations on Treponema pallidum 23S rRNA gene by nested multiplex polymerase chain reaction (Faculty of Medicine Universitas Indonesia, 2017)
Background: Azithromycin-resistant strains of Treponema pallidum is associated with the mutation of 23S rRNA gene of T. pallidum. Although these strains are now prevalent in many countries, there is no laboratory test kit to detect and identify these mutations. Thus, in this study we developed a nested multiplex polymerase chain reaction (PCR) to detect and identify A2058G and A2059G mutations in 23S rRNA gene. Methods: Three primer sets were designed for nested PCR reactions. To obtain maximum PCR reaction, all parameters were optimized. The specificity of the primer sets was evaluated towards some microorganisms. A sensitivity test was conducted to get detection limit of deoxyribonucleic acid (DNA). Forty-five whole blood specimens were tested by PCR, and positive results were confirmed by the DNA sequencing. Results: The assay could detect at least 4,400 DNA copy number and showed no cross reaction with other microorganisms used in the specificity test. A total 13 of 45 whole blood specimens were PCR positive for T. pallidum, and no single mutations (either A2058G or A2059G) were detected. Two positive specimens were confirmed by the DNA sequencing and showed no mutation. Conclusion: Nested multiplex PCR developed in this study showed a specific and sensitive test for the detection and identification of A2058G and/or A2059G mutations of 23S rRNA T. pallidum gene.